2022
DOI: 10.1021/acssynbio.1c00471
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Amber Suppression via Ribosomal Skipping for In Situ Synthesis of Photoconditional Nanobodies

Abstract: Genetic code expansion is a versatile method for in situ synthesis of modified proteins. During mRNA translation, amber stop codons are suppressed to site-specifically incorporate non-canonical amino acids. Thus, nanobodies can be equipped with photocaged amino acids to control target binding on demand. The efficiency of amber suppression and protein synthesis can vary with unpredictable background expression, and the reasons are hardly understood. Here, we identified a substantial limitation that prevented sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 84 publications
0
17
0
Order By: Relevance
“…[32] Furthermore, photo-caging of eNB using ONBY or NPY resulted in blocking of target binding when nanobody and target were coexpressed in cultured HeLa cells. [36,37] While ONBY was not sufficient to abolish binding in our intracellular assay, we found that uncaging by illuminating animals using a 365 nm LED (640 seconds illumination, 10 mW/…”
Section: Npy and Onby Substitution Is Not Sufficient To Photocage Ant...mentioning
confidence: 75%
See 4 more Smart Citations
“…[32] Furthermore, photo-caging of eNB using ONBY or NPY resulted in blocking of target binding when nanobody and target were coexpressed in cultured HeLa cells. [36,37] While ONBY was not sufficient to abolish binding in our intracellular assay, we found that uncaging by illuminating animals using a 365 nm LED (640 seconds illumination, 10 mW/…”
Section: Npy and Onby Substitution Is Not Sufficient To Photocage Ant...mentioning
confidence: 75%
“…This observation was unexpected since previously published in vitro binding assays, using photocaged eNB purified from E. coli , showed that Y37 substitution for ONBY reduces binding affinity 10,000 fold and blocks binding in vitro , and NPY reduces binding affinity 420 fold [32] . Furthermore, photo‐caging of eNB using ONBY or NPY resulted in blocking of target binding when nanobody and target were co‐expressed in cultured HeLa cells [36,37] …”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations